Implementasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Kemuhammadiyahan di MTs Muhammadiyah Kota Bengkulu - Rasidin Ahmad Saputra; Zubaedi Zubaedi (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of study This that is For know planning, steps and influence implementation values moderation religious in learning Muhammadiyah at MTs Muhammadiyah Bengkulu City and relevance learning Muhammadiyah to mark moderation religious. Types of research is study qualitative. Data collection using technique interviews, observations, documentation. Study This conclude that: 1) Planning learning in apply values moderation religion on learning Muhammadiyah started with decision head of the based madrasah to technical guidelines from republican ministry of religion Indonesia. Then applied in madrassa based on decision foundations, madrasa heads and teacher councils through device learning, like syllabus, prota, process and lesson plans. 2) Implementation steps values moderation religious in learning Muhammadiyah done through approach history, personality, beliefs, and ideals life, organization, charity efforts, roles and practices organize. 3) Influence values moderation religious in learning Muhammadiyah very OK, p That seen from mark results Study students and the learning process within class, student more can behave tolerance to opinion his friends are different and more can accept their differences meet in society.